2013
DOI: 10.1016/j.drugalcdep.2012.11.021
|View full text |Cite
|
Sign up to set email alerts
|

The alpha-1 adrenergic antagonist doxazosin for treatment of cocaine dependence: A pilot study

Abstract: Background Medications decreasing central noradrenergic activity have been associated with attenuation of cocaine effects. Aims This pilot study examined the efficacy of doxazosin versus placebo for reducing cocaine use in treatment-seeking cocaine dependent persons. Methods We screened 108 cocaine dependent subjects and assigned 35 participants to receive either doxazosin (8mg/day) or placebo for 13 weeks. Participants were titrated on the study medication according to two different schedules. During the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 34 publications
3
44
0
Order By: Relevance
“…On the other hand, animals lacking α1 NE receptors in cortex or striatum show reduced sensitivity to the reinforcing effects of opiates and stimulants [143-145]. Further, treatment with NE a1 receptor antagonists attenuated cocaine reinstatement [140,146], reduced subjective effects produced by cocaine [147], and reduced cocaine-use in a preliminary study [148]. Similarly, serotonin attenuates cocaine-induced increases of DA in monkeys [149], which suggests that medications that increase DA, NE and serotonin (i.e., triple reuptake inhibitors) may prove efficacious.…”
Section: Expert Opinionmentioning
confidence: 99%
“…On the other hand, animals lacking α1 NE receptors in cortex or striatum show reduced sensitivity to the reinforcing effects of opiates and stimulants [143-145]. Further, treatment with NE a1 receptor antagonists attenuated cocaine reinstatement [140,146], reduced subjective effects produced by cocaine [147], and reduced cocaine-use in a preliminary study [148]. Similarly, serotonin attenuates cocaine-induced increases of DA in monkeys [149], which suggests that medications that increase DA, NE and serotonin (i.e., triple reuptake inhibitors) may prove efficacious.…”
Section: Expert Opinionmentioning
confidence: 99%
“…For example, the a1AR antagonist doxazosin decreased self-report of "high," "stimulating," and "like cocaine" after cocaine administration (20 mg/kg i.v. ; Newton et al, 2012) and increased cocaine-negative urines in treatment-seeking cocaine-dependent people compared with placebo under some dosing regimens (Shorter et al, 2013). These results indicate a need for further investigation of the promising therapeutic capabilities of a1AR antagonists.…”
Section: Self-administrationmentioning
confidence: 96%
“…On the basis of recent studies implicating NE in relapse-like behavior, interest in the contribution of this neurotransmitter to addictive processes has reemerged (Weinshenker and Schroeder, 2007;Gaval-Cruz and Weinshenker, 2009). Some noradrenergic compounds have already shown promise in human laboratory studies and initial clinical trials (Gaval-Cruz and Weinshenker, 2009;Fox et al, 2012;Haile et al, 2012;Newton et al, 2012;Shorter et al, 2013;K. Cunningham, personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…In preclinical trials, pharmacologic antagonism of the noradrenergic system has been shown to limit the behavioral effects of stimulants, including amphetamine and cocaine [54,57,82], and to attenuate cocaine-induced reinstatement of cocaine-seeking behavior in rats [83,84]. In a recent pilot trial of 35 cocaine-dependent individuals, doxazosin 8 mg/day, administered according to two titration schedules (slow --8 weeks vs fast --4 weeks) was compared to placebo [85]. The group receiving doxazosin according to the fast titration schedule demonstrated a significant increase in percentage of total cocaine-negative urines (35% for doxazosin-fast vs 10% for doxazosin-slow and 14% for placebo; x 2 = 36.3, df = 2, p < 0.0001).…”
Section: Noradrenergic Agents 521 Doxazosinmentioning
confidence: 99%